2018
DOI: 10.1088/1681-7575/aac441
|View full text |Cite
|
Sign up to set email alerts
|

Reply to ‘Dynamic phase shift within a falling glass cube is negligible: comment on ‘Relativistic theory of the falling cube gravimeter’’

Abstract: In the subject paper Ashby (2018 Metrologia 55 1-10) of the comment Svitlov (2018 Metrologia 55 609-13), light propagation through an absolute gravimeter was analyzed, including the propagation delay through the falling retroreflector and through the vacuum. The resulting expression for the interference signal applies without any subsequent 'speed of light' correction. Other corrections appeared for the three fitting parameters Z 0 , V 0 and g, which are, respectively, the initial position and velocity, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…According to (7), the error affecting the estimated ḡ value in a real operational condition, i.e. D = 0.0175 m, was 7.76 × 10 −5 µGal and 7.83 × 10 −5 µGal (1 µGal = 1 × 10 −8 m s −2 ) in the direct free-fall and symmetric rise-and-fall case, respectively, whereas in the fictitious operational condition, i.e.…”
Section: Simulation and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (7), the error affecting the estimated ḡ value in a real operational condition, i.e. D = 0.0175 m, was 7.76 × 10 −5 µGal and 7.83 × 10 −5 µGal (1 µGal = 1 × 10 −8 m s −2 ) in the direct free-fall and symmetric rise-and-fall case, respectively, whereas in the fictitious operational condition, i.e.…”
Section: Simulation and Data Processingmentioning
confidence: 99%
“…The subject was extensively discussed in several comments and replies without reaching a final agreement [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…( 1) is the basis for the present study. The apparently large effect on g arising from dimensions and refractive index of the cube resulted in several critical comments [2,3,4], and replies [5,6,7], without throwing light on the real issues.…”
Section: Introductionmentioning
confidence: 99%
“…This expression is the basis for the present study. The apparently large effect on g arising from dimensions and refractive index of the cube resulted in several critical comments [2][3][4], and replies [5][6][7], without throwing light on the real issues. D'Agostino [8] simulated dropping of glass and open retroreflectors using only the difference ϕ(t)−ϕ(0) for the interference observations.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming D=1.75 cm, γ = 307 E ‡, n=1.57, d = D/4 [1], the effect reaches the value of 7 µGal §. Several authors have found problems with the reasoning substantiating the effect [2,3,4], but the arguments of the critique were declined [5,6,7,8]. The discussed issue directly affects the realisation of the new definition of the base SI unit of mass, the kilogram [9,10], therefore, the question of the existence of the effect needs to be resolved.…”
Section: Introductionmentioning
confidence: 99%